Quantification of parvalbumin in commercially important Mediterranean seafood species using real time PCR - Dimitra HOUHOULA; Polytimi DIMITRIOU; Gena MENGJEZI; Vasiliki KYRANA; Vladimiros LOUGOVOIS (Czech Journal of Food Sciences, 2015)
The parvalbumin allergen gene was quantified in various types of seafood using RT PCR. Freshly harvested specimens from 25 species of finfish, molluscs, and crustacean shellfish, commonly consumed in the Mediterranean region, were included in the investigation. DNA was extracted using the commercial NucleoSpin Food kit. The amplification of the parvalbumin gene was performed by RT PCR. Sixteen out of the 25 species examined yielded positive amplification. Positive samples, including several species of fish (Atlantic mackerel, horse mackerel, sheepshead, red mullet, sandsmelt, pandora, saddled sea bream, gilthead sea bream, red sea bream, European sea bass, blue whiting, anchovy, sardine) and cephalopods (cuttlefish, musky octopus), exhibited largely variable thresholds differing by as much as 12 cycles. Even though equal amounts of DNA were used in PCR amplification the copy number of gene-encoded parvalbumin varied between the fish species. The assay proved to be a potential tool for the detection and label management of fish allergens in food. The studies have shown that allergic reactions to food are highly individual. For some hypersensitive patients, even trace amounts can cause life-threatening allergic reactions. The results of the present study indicate that several seafood species, commonly consumed in the Mediterranean region, may pose a threat for hypersensitive individuals.